Active‐Site Targeting Paramagnetic Probe for Matrix Metalloproteinases. Issue 12 (11th October 2016) - Baldoneschi, Veronica; Cerofolini, Linda; Dragoni, Elisa; Storai, Andrea; Luchinat, Claudio; Fragai, Marco; Richichi, Barbara; Nativi, Cristina
Abstract: The design and synthesis of the Ln 3+ complexes of a DOTA‐containing (DOTA=1, 4, 7, 10‐tetraazacyclododecane‐1, 4, 7, 10‐tetraacetic acid) inhibitor of matrix metalloproteinases are reported. The tight binding of the sulfonamide scaffold to the catalytic domain of the investigated matrix metalloproteinase is not impaired by the presence of the Ln 3+ ‐DOTA moiety. The paramagnetic properties of the Ln 3+ complex are exploited to obtain insights into the structural features of the ligand–protein interactions and to evaluate the influence of the linker length on the quality of the paramagnetic restraints. Abstract : Structural probes : Paramagnetic probes are useful tools for protein targeting and drug discovery. Targeting of pathologically overexpressed zinc enzymes can be afforded easily with sulfonamide‐based inhibitors bearing a zinc‐binding group for the catalytic domain and a paramagnetic ligand to investigate the structural features of the protein–ligand interactions (see figure).